Upaya Peningkatan Branding Produk UMKM Es Cendol Berbasis Ekonomi Kreatif Melalui Foto Produk - Yogi Pratama Putra; Ahmad Nidhom Mahyuddin; Ari Widian Agustina; Rena Arriva Dwi Nnisaul Hotimah; Oktavia Pramastasari; Stevi Putri Adolvina Baik; Dewi Puspa Arum (Jurnal Informasi Pengabdian Masyarakat, 2023)
MSMEs are the initial pillar of economic development in Indonesia, various efforts have been made by the government. The creative economy is a government program concept that aims to increase MSMEs in Indonesia. Product branding is part of innovation and creativity in increasing the value of a product. The purpose of this journal is to brand Cendol Suji UMKM products with a product branding strategy through product photos. This activity uses the method of observation, interviews, and the use of technology. MSME empowerment activities through product photo assistance starting from the product photoshoot process to the editing process. This is expected to provide new insights for MSME players to brand their products so they can compete in the free market.